KARAKTERISTIK KERATITIS NUMMULARIS DI RSUD DR. SOEDARSO PONTIANAK JANUARI 2010-DESEMBER 2012 - ., Vicky Victorine Persia Wardenaar (Jurnal Mahasiswa PSPD FK Universitas Tanjungpura, 2013)
Background. Nummular keratitis can cause serious impaired vision if there is notany prompt treatment and prevention. There was not any data aboutcharacteristic of nummular keratitis in dr. Soedarso General Hospital Pontianak.Objective. To know about characteristic of nummular keratitis in dr. SoedarsoGeneral Hospital Pontianak on 2010 2012.Metodology. This study was a descriptive observational study with crosssectionaldesign.The samplethat usedin this study are 70 patients. Data weretakenfromthepatient's medicalrecord.Result. The most common age group who have nummular keratitis was 28-35years old as many as 14 patients. The number of male patients with nummularkeratitis were 36 patients and woman were 34 patients. There were 56 patients ofnummular keratitis who experience impaired vision and 14 patients had a normalvision. There were 18 patients of nummular keratitis with corneal traumaexperience, and 52 patients who did not have any corneal trauma experience.Nummular keratitis were more often found on students, as many as 15 patients.Unilateral nummular keratitis was found in 58 patients.Conclusion. Patients with nummular keratitis who had given treatment in dr.Soedarso general hospital had characteristic that were most common age groupwas 28-35 years old (20,00%); more often found on male patients (51,40%);more experience impaired vision (80,00%); 74,30% patients never experiencecorneal trauma and unilateral nummular keratitis (82,90%) was more commonthan bilateral nummular keratitis (17,10%).Keywords : Nummular keratitis, incidence, corneal trauma